PENGARUH METODE TOTAL PHYSICAL RESPONSE (TPR) DALAM MENINGKATKAN VOCABULARY UNTUK MAHAMAHASISWA KEPERAWATAN DI INSTITUT KESEHATAN DELI HUSADA DELI TUA - GINTING, SULASTRI; Hariati, Hariati (Jurnal Inovasi Kesehatan Masyarakat, 2020)
The research aims to measure the effect of total physical response method for Health Information Management students at Health Institute of Deli Husada Deli Tua. The study method used quantitative approach to find out the answer of the problem of study. There were two classes be coming sample of study namely Nursing 2A as experiment group and Nursing 2B as control group with the total number students of each classes are 35. The sample of study is determined using population sampling technique. Both groups were given pre- test before treatment. Then, the student of experiment group was taught by TPR and control group was taught without TPR. Finally, the writer gave post-test to both groups. Based on the calculation above, the writer found out that the mean score of the experimental group (3-A) was 61.67 and the means score of the control group (3-C) was 52.27. With the level of significance at 5%, the writer found out that the observed t (to) was 1.85. Since to is greater than the table, Ho is rejected and Ha is accepted. It meant that total physical response gives effect on the students’ vocabulary size of the nursing students at Health Institute of Deli Husada Deli Tua.